Self, social structure, and beliefs : explorations in sociology - Alexander, Jeffrey C., 1947-; Marx, Gary T.; Williams, Christine L., 1959- (University of California Press, 2004)
Neil Smelser is an iconic figure in sociology. This volume reveals the range & depth of his influence, & his substantial contributions to diverse fields such as British history, social change, collective behaviour, higher education, the economy, & psychoanalysis.